Praktik Dagang di Pakan Serikat Koto VII Basambilan Koto, Sijunjung (1980-1998) - Irawanti, Pungki (Jurnal Ceteris Paribus, 2024)
This research aims to analyze how traditional markets shape local capitalist practices in Pakan Serikat Koto VII Basambilan Koto, Sijunjung, from 1980 to 1998. The research employs a historical method with four stages: heuristics, criticism, interpretation, and historiography. The research findings demonstrate that traditional markets have shaped local capitalist practices in Pakan Serikat Koto VII Basambilan Koto. These practices manifest in various forms, including trading systems, social relations, cultural exchange, and social change. The establishment of Pakan Serikat VII Koto has driven social change in the community, such as changes in livelihood systems and lifestyles. The research concludes that traditional markets play a crucial role in shaping local capitalist practices in Pakan Serikat Koto VII Basambilan Koto. Traditional markets serve not only as places for exchanging goods and services but also as venues for social interaction, cultural exchange, and social change. Keywords: Traditional market, Local capitalism, Pakan Serikat Koto VII Basambilan Koto, Sijunjung, 1980-1998